Emotional Experience: The Psychological Mechanism of Issue-based Teaching in Promoting Core Literacy in Ideological and Political Subjects among Middle School Students - Wang, Weiyi (International Journal of Public Health and Medical Research, 2026)
In the context of education reform oriented towards core competencies, ideological and political education in middle schools is undergoing a transformation from knowledge imparting to the cultivation of abilities and values. To deeply reveal the psychological mechanism by which emotional experience is transformed into political identity and internalization of values in issue-based teaching, this study takes "emotional experience" as the core mediating variable and explores its role in promoting the generation of core literacy in the subject of ideological and political education for middle school students through issue-based teaching. The study shows that problem-based teaching achieves the goal of cultivating core competencies through the psychological path of "cognitive conflict - emotional experience - value internalization". Cognitive conflict is the starting point of teaching, emotional arousal is the key link in the cultivation of core literacy "awareness", and emotional resonance promotes value internalization and behavioral transfer. Based on the findings of this study, an emotional experience-driven teaching strategy is proposed, covering the construction of life-related and conflict-related issue situations, emotional regulation led by cognitive reassessment, and step-by-step reflection guidance. The three form a closed-loop system, which can not only exert the dynamic efficacy of emotional experience, but also ensure the correctness of value orientation through cognitive reassessment and reflective guidance, providing theoretical basis and practical approach for the implementation of the core literacy of political science in issue-based teaching.